Telkomsel Siaga RAFI Annual Event Strategy to Improve Brand Image by Senusa Indonesia - Manalu, Margareta; Khotimah, Qusnul; Zacharias, Alain Rishi (Journal of Indonesian Tourism and Policy Studies, 2025)
This research aims to analyze the strategy of Telkomsel Siaga RAFI annual event organized by Senusa Indonesia in order to improve Telkomsel's brand image. Through this activity, Telkomsel seeks to strengthen relationships with customers and expand its social reach, especially during Ramadan and Idul Fitri 2025. The main focus of this final report is to explore the role of event management strategies in influencing the brand image of Telkomsel. Using brand image theory and direct observation techniques, this research also identifies the steps taken by Senusa Indonesia in designing and implementing events that include knowledge sharing and donations. The results showed that the event not only improved Telkomsel's image as a socially conscious brand, but also strengthened customer loyalty through their active involvement in social campaigns.